Generating Non-redundant Multilevel Association Rules Using Min-max Exact Rules - R. Vijaya Prakash; S. S. V. N. Sarma; M. Sheshikala (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Association Rule mining plays an important role in the discovery of knowledge and information. Association Rule mining discovers huge number of rules for any dataset for different support and confidence values, among this many of them are redundant, especially in the case of multi-level datasets. Mining non-redundant Association Rules in multi-level dataset is a big concern in field of Data mining. In this paper, we present a definition for redundancy and a concise representation called Reliable Exact basis for representing non-redundant Association Rules from multi-level datasets. The given non-redundant Association Rules are loss less representation for any datasets.